Memorandum of Understanding between the James P. Grant School of Public health, BRAC University, Dhaka, Bangladesh and Karolinska Institutet, Stockholm, Sweden (2008) - James P. Grant School of Public Health, BRAC University; Karolinska Institute, Stockholm (BRAC University and Karolinska institutet, 2013)
Memorandum of Understanding between the James P. Grant School of Public Health, BRAC University, Dhaka, Bangladesh and Karolinska Institutet, Stockholm, Sweden.